Exploration of the Osteoarthritis Health, Illness and Treatment Beliefs of New Zealanders With Hip and/or Knee Osteoarthritis and the Clinicians Who Treat the Condition - O'Brien, Daniel (Auckland University of Technology, 2018)
Osteoarthritis is a chronic musculoskeletal condition that commonly affects physical, social and mental well-being. Adherence to conservative treatments for hip and knee joint osteoarthritis is poor and known to be affected by health, illness and treatment beliefs of people with the condition and the beliefs of the clinicians who treat these people. Despite this knowledge, few studies have explored and compared the osteoarthritis health, illness and treatment beliefs of people with the condition and clinicians, and no known research to date has explored this in the New Zealand healthcare context. Therefore, one aim of this thesis was to identify, compare and contrast the osteoarthritis beliefs held by New Zealanders living with hip and/or knee osteoarthritis and the beliefs of the clinicians who treat people with this condition. The other aim of the thesis was to identify if people’s and clinicians’ osteoarthritis beliefs could be measured by existing questionnaires that are grounded in theoretical health, illness and treatment belief models. The research component of this thesis consisted of two strands, both of which followed an exploratory, sequential mixed-methods design. The first explored the beliefs of people with osteoarthritis, and the second explored clinicians’ beliefs. Each strand followed the same format and consisted of three studies; a qualitative descriptive study, a systematic literature review, and a cross-sectional survey. Twelve people with hip and/or knee osteoarthritis were recruited to the study of people’s osteoarthritis health, illness and treatment beliefs. Thematic analysis of the data identified four themes that were called: (i) Knowing the cause but not the consequence; (ii) Explaining treatment beliefs; (iii) Understanding the importance of clear collaborative care; and (iv) Meaning more than just the joint. Comparison of these themes with existing models of health, illness and treatment beliefs indicated that the themes had notable overlap with many of the constructs contained within the Common Sense Model (CSM). A systematic literature review identified 17 potential questionnaires. Only the Illness Perception Questionnaire-Revised (IPQ-R) and the Knee Osteoarthritis Fears and Beliefs Questionnaire (KOFBeQ) met the criteria for inclusion in the survey. Items of the KOFBeQ were modified so that the measure was appropriate for people with knee and hip osteoarthritis. One hundred and ninety-eight people with hip and/or knee osteoarthritis completed the survey. The results of this study suggest the IPQ-R and the adapted KOFBeQ have the potential to be valid and reliable measures of osteoarthritis health, illness and treatment beliefs for people with hip and/or knee osteoarthritis, but limitations with both questionnaires were identified. Eleven clinicians (2 general practitioners, 2 orthopaedic surgeons, 5 physiotherapists, 1 rheumatologist, and 1 sports physician) were recruited to the qualitative descriptive study of clinicians’ osteoarthritis health, illness and treatment beliefs. Thematic analysis of the data identified four themes that were called: (i) Matching each patient’s signs and symptoms; (ii) Anticipating what patients think; (iii) Enabling patients to understand their osteoarthritis and find their treatment path; and (iv) Understanding that treatment only works when everyone is engaged. Comparison of these themes with existing models of clinicians’ health, illness and treatment beliefs and clinical practice approaches, revealed some similarities with the Biomedical and Biopsychosocial Models. A second systematic literature review identified 11 potential questionnaires, but only the Pain and Attitudes Beliefs Scale for Physiotherapists (PABS-PT) questionnaire met the criteria for inclusion in the survey. The PABS-PT did not explore all of the themes identified in the qualitative study of clinicians’ beliefs. Therefore, a further search of the literature identified a clinical vignette about a person living with moderate knee osteoarthritis. Additionally, the KOFBeQ was adapted for use with the clinicians, and both measures were included in the survey. Two hundred and ninety-five clinicians (87 general practitioners and 208 physiotherapists) took part in the survey. The findings highlighted considerable limitations in the PABS-PT questionnaire and some limitations with the Clinicians’ KOFBeQ. The osteoarthritis health, illness and treatment beliefs of clinicians appeared similar to best practice guidelines, but some of the results indicated limitations in current osteoarthritis clinical services. Three conclusions emerged from the research component of this thesis. First, people with hip and/or knee osteoarthritis and clinicians who manage the condition hold similar and conflicting beliefs about the disease. Second, the current questionnaires used to measure the osteoarthritis health, illness and treatment beliefs of people with hip and/or knee osteoarthritis and clinicians who treat the condition are limited. Third, the health, illness and treatment beliefs of both people with hip and/or knee osteoarthritis and clinicians who treat the condition were not fully explained by existing health, illness and treatment beliefs models. A shared model of osteoarthritis beliefs was proposed as a theoretical framework that has the potential to overcome the limitations of existing osteoarthritis health, illness and beliefs models and improve clinical services for people living with the condition
Keywords: Osteoarthritis; Health and illness beliefs; Treatment beliefs; Patients; Clinicians